ANALYSIS OF LIQUIDITY RATIOS IN ISLAMIC BANKS IN INDONESIA - Reza santika; Rizka Ayuni; Titin Trisnawati (Publikasi Inspirasi Indonesia, 2024)
This article examines the liquidity of Bank Syariah Indonesia through financial ratio analysis in the 2018-2022 financial statements using the liquidity ratio approach. The results of the liquidity analysis of Bank Syariah Indonesia from 2018-2022, in general, can be said that the bank's performance is quite good. This can be seen from the fluctuations in the Current Ratio, Quick Ratio, and Cash Ratio achieved by the company. Keywords: liquidity analysis, Islamic banks, financial ratios,